(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
This paper aims to analyze and improve information management in an organization that provides health services in the city of Mar del Plata, Argentina. The main problem it presents is the lack of a comprehensive information system that allows improving decision-making and the efficiency of central and support processes. That is why it is proposed to apply the value stream mapping tool to identify the activities that do not generate value to the current processes, in relation to the generation and management of information, and the opportunities for improvements that contemplate the incorporation of a management software with specific development requirements. The proposed changes are implemented and a value mapping of the improved processes is carried out to study comparatively the current situation and the proposal. The implementation of the improvements made it possible to increase the availability of timely information for decision-making, simplify the tasks of the staff and reduce unproductive time.